2019
DOI: 10.1007/s11192-019-03065-4
|View full text |Cite
|
Sign up to set email alerts
|

The age at which Noble Prize research is conducted

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 16 publications
0
8
0
1
Order By: Relevance
“…These documents contains references to the award-winning works of the Laureates, as well as references to background scientific works relevant for the awarded Nobel Prize. These references has previously been analyzed for all Nobel Prize fields to reveal the average age of Nobel Laureates when their Nobel Prize-awarded research was conducted, the number of works cited by the Nobel Foundation for each Laureate and the waiting time between conducting Nobel Prize-awarded research and receiving the Nobel Prize [18].…”
Section: Methods and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These documents contains references to the award-winning works of the Laureates, as well as references to background scientific works relevant for the awarded Nobel Prize. These references has previously been analyzed for all Nobel Prize fields to reveal the average age of Nobel Laureates when their Nobel Prize-awarded research was conducted, the number of works cited by the Nobel Foundation for each Laureate and the waiting time between conducting Nobel Prize-awarded research and receiving the Nobel Prize [18].…”
Section: Methods and Resultsmentioning
confidence: 99%
“…To explore this, we consider the years 1995-1999 as this is the five-year period with the highest number of cited works from both Nobel Laureates and background scientific publications in the Scientific Background material. The time between conducting the Nobel Prize-awarded research and being awarded the Nobel Prize is on average 23.5 ± 14.0 years in physics [18], which means that publications after this period have not fully had time to be cited in the Nobel Prize Scientific Background material, i.e. future Nobel Prizes will likely be awarded for scientific discoveries conducted after this period.…”
Section: Impact Factormentioning
confidence: 99%
“…At present, there are two explanations for the relationship between age and scientific research output of talents: First, some scholars reckon that the best creative age for the scientific elites presents the unimodal shape. Taking the age distribution of Nobel laureates as an example, physics laureates are younger than scientists in the field of economics (Bjork, 2019). Studies have found that the age of the highest professional achievement of top scientists gradually shifts back, and the peak age of scientific research is also moving backward (Jones and Weinberg, 2011).…”
Section: Personality and Talent Selectionmentioning
confidence: 99%
“…The average age of men and women when receiving the Nobel Prize is 71 for chemistry, 67 for economics, 68 for physics, and 68 for physiology or medicine during 2010-2019(Bjørk, 2019).Downloaded from http://direct.mit.edu/qss/article-pdf/doi/10.1162/qss_a_00148/1930834/qss_a_00148.pdf by guest on 09 August 2021…”
mentioning
confidence: 99%